Pengaruh Metode Latihan Drill Terhadap Keterampilan Dribble Bola Basket Pada Ekstrakurikuler di SMP Negeri 1 Lemahabang - Bulan Antartika Rahma Putri; Astri Ayu Irawan; Dhika Bayu Mahardika (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to determine the effect of the drill training method on students' dribble skills in the basketball extracurricular at SMP Negeri 1 Lemahabang. This research is an experimental research to find out whether the effect of the drill training method on basketball dribble skills. The number of students who were sampled was 30 people who were taken using the Sjenus sempling technique where all the population was used as the sample. The research data was carried out with a one group pretest-posttest design using a test of students' dribble skills. The results of the research were obtained through a data normality test with the results stating that the pretest data was 0.102 > 0.05 and the posttest was 0.177 > 0.05. the results of the pretest-posttest stated that the data had a homogeneous distribution and the t-test calculation obtained the Sig. (two-tilled) 0.000 <0.05 indicates a significant difference between the results before and after being given treatment. It can be concluded that from the results of the research conducted, it can be stated that there is an influence of the drill training method on basketball dribble skills in extracurricular activities at SMP Negeri 1 Lemahabang.